KONSEP PEMIKIRAN WASFI ASYUR ABU ZAID TERHADAP MAQASHID AL-QUR’AN - Rindy Pratiwi; Pakhrur Rozi; Shofyan Harahap; Laila Sari Masyhur (Jurnal Syaikh Mudo Madlawan: Kajian Ilmu-Ilmu Keislaman, 2025)
This research discusses the concept of Maqashid al-Qur’an as the purpose and intent of Allah SWT in every verse of the Qur’an, whether it contains legal rulings or non-legal moral messages. The main focus of the research is the thoughts of Wasfi Asyur Abu Zaid in developing a moderate and constructive maqasidi interpretation approach, as a response to the challenges of textualist and contextualist critiques of the Qur'an. The method used is library research with a qualitative approach, analyzing Abu Zaid's main works as well as other supporting literature. The research results show that maqasidi interpretation integrates textual and rational approaches in exploring the meaning and purpose of Quranic verses holistically, with a focus on the welfare of the community and the relevance to the modern context. This interpretation emphasizes the importance of understanding maqashid at various levels, from words, verses, chapters, to the main themes of the Qur'an. Thus, this approach provides a new scientific and solution-oriented methodological framework for the interpretation of the Qur'an in the contemporary era.